Root parasitic plant Orobanche aegyptiaca and shoot parasitic plant Cuscuta australis obtained Brassicaceae-specific strictosidine synthase-like genes by horizontal gene transfer - Zhang, Dale; Qi, Jinfeng; Yue, Jipei; Huang, Jinling; Sun, Ting; Li, Suoping; Wen, Jian-Fan; Hettenhausen, Christian; Wu, Jinsong; Wang, Lei; Zhuang, Huifu; Wu, Jianqiang; et al. (My University, 2014)
Background Besides gene duplication and de novo gene generation, horizontal gene transfer (HGT) is another important way of acquiring new genes. HGT may endow the recipients with novel phenotypic traits that are important for species evolution and adaption to new ecological niches. Parasitic systems expectedly allow the occurrence of HGT at relatively high frequencies due to their long-term physical contact. In plants, a number of HGT events have been reported between the organelles of parasites and the hosts, but HGT between host and parasite nuclear genomes has rarely been found. Results A thorough transcriptome screening revealed that a strictosidine synthase-like (SSL) gene in the root parasitic plant Orobanche aegyptiaca and the shoot parasitic plant Cuscuta australis showed much higher sequence similarities with those in Brassicaceae than with those in their close relatives, suggesting independent gene horizontal transfer events from Brassicaceae to these parasites. These findings were strongly supported by phylogenetic analysis and their identical unique amino acid residues and deletions. Intriguingly, the nucleus-located SSL genes in Brassicaceae belonged to a new member of SSL gene family, which were originated from gene duplication. The presence of introns indicated that the transfer occurred directly by DNA integration in both parasites. Furthermore, positive selection was detected in the foreign SSL gene in O. aegyptiaca but not in C. australis. The expression of the foreign SSL genes in these two parasitic plants was detected in multiple development stages and tissues, and the foreign SSL gene was induced after wounding treatment in C. australis stems. These data imply that the foreign genes may still retain certain functions in the recipient species. Conclusions Our study strongly supports that parasitic plants can gain novel nuclear genes from distantly related host species by HGT and the foreign genes may execute certain functions in the new hosts.
Keywords: Cuscuta, Horizontal gene transfer, New genes, Orobanche, Parasitic plants, Strictosidine Synthase-Like Genes